Early evidence for beer drinking in a 9000-year-old platform mound in southern China. - Jiajing Wang (Public Library of Science (PLoS), 2021)
Alcoholic beverages played an essential role in rituals in ancient societies. Here we report the first evidence for beer drinking in the context of burial ritual in early Holocene southern China. Recent archaeological investigations at Qiaotou (9,000-8,700 cal. BP) have revealed a platform mound containing human burials and high concentrations of painted pottery, encircled by a human-made ditch. By applying microfossil (starch, phytolith, and fungi) residue analysis on the pottery vessels, we found that some of the pots held beer made of rice (Oryza sp.), Job's tears (Coix lacryma-jobi), and USOs. We also discovered the earliest evidence for using mold saccharification-fermentation starter in beer making, predating written records by 8,000 years. The beer at Qiaotou was likely served in rituals to commemorate the burial of the dead. Ritualized drinking probably played an integrative role in maintaining social relationships, paving the way for the rise of complex farming societies four millennia later.